A view through the long lens: Pre-service teachers' perceptions of multi-campus course delivery - Walker-Gibbs, Bernadette; Paatsch, Louise; Moles, Janet; Yim, Bonnie; Redpath, Terri (Journal of University Teaching and Learning Practice, 2016)
This paper explores the results of a survey that was conducted with 277 pre-service teachers studying at two regional university campuses in Victoria, Australia in 2014. Data showed that participants expressed high level of satisfaction with the quality of their undergraduate courses in education including the flexible teaching and learning experiences. However, many reported experiencing frustration with accessing cloud-based learning materials and support services, including communication with lecturers. Challenges in accessing learning materials were mainly attributed to slow internet speed which increased the time taken to download resources. Access to support services and lecturers was made difficult because many key staff were located at the larger, urban campuses, thus sometimes causing delay in communication with them.This study recommends that university faculties review the accessibility of services, facilities and resources for rural and remote students. Recommendations include greater attention to the presentation of online learning materials to ensure accessibility for all students, regardless of internet speed and location. Moreover, findings showed that by closer examination of the accessibility of services to reflect the reality and complexity of students’ lives, universities could increase equity for rural and remote students.